The Soundness of Female Teacher’s Dress Code Policy in Sri Lanka - Prabodha Rathnayake; Chamarie Jayasinghe (International Journal of Education, Teaching, and Social Sciences, 2023)
Clothing plays a crucial role in any society as an indicator to reflects the personality, culture, subcultures, religions, occupations, and moral values of individuals. The debate between formal and informal dress code in labor market is being a serious deliberation to many scholars. Especially, teachers are subjected to such discussions, because a teacher is considered to be a role model to students. In addition, the dress of teachers may have different implications than other professions. Since, the dress code replicates the set of principles in an organization comprising with the professionalism, such policies should be more important and proactive. Recently, different parties in Sri Lanka confronted with controversial ideas regarding female teacher’s dress code. However, the existing policies were not reformed and not considerably measured the relationship between job performance and employee attire by relevant authorities in Sri Lanka. Thus, to examine the soundness of prevailing dress code policy, the study is surveyed the positive and negative impacts of job performance that female teachers encounter due to dress code policy in Sri Lanka. Further, the study identified certain best practices that could imply to modernize the existing traditional dress code policies. The study was carried out as a qualitative study using in-depth interviews with individuals and group discussions. Fifteen participants were selected as the sample based on judgmental sampling method while thematic analysis was used to analyze the collected data. Based on the results of interviews, three themes were discussed as the outcomes of the study including effect of attire on professionalism, school culture and professional attire, and the challenges of wearing professional attire. The study emphasized the importance of adjusting existing dress code policy for female teachers in Sri Lanka by adhering the challenges on job performance by the attire.